Well-being in parents of children with cancer: illness perceptions’ mediating role for hope and social support - Schwartz-Attias, Irit; Krulik, Tamar; Ronen, Tammie (Frontiers in Psychology, 2024)
Introduction: Parents of children with cancer may experience enormous physical and emotional pressures. During such times, perception of the situation can be important in mediating the link between one's basic resources (mainly cognitive and social) and the well-being one attains as an emotional and cognitive response. This study aimed to explore the role of illness impact perceptions in mediating the link between hope, social support and subjective well-being in parents of children with cancer. Methods: The cross-sectional study included 108 parents of children aged 7-18 diagnosed with cancer at least 6 months prior to the study. The parents completed one questionnaire comprising five instruments: perceived impact of illness, hope, social support, positive and negative affect (the emotional component of well-being) and life satisfaction (the cognitive component of well-being). Descriptive statistics and Pearson correlations were conducted for all study variables. SEM analysis was performed to examine the study’s theoretical model. Results: The current sample included 108 parents of children with cancer recruited from two pediatric hematology-oncology wards in two different hospitals in central Israel. Most participants were mothers (70.4%), and the mean age was 44.46. The main results indicated that hope and social support correlated negatively with perceptions of the illness’ impact. Illness impact perceptions mediated the relations between hope, social support and positive emotions, which means that when the parents perceived their child’s illness as less impactful on the family, they experienced higher levels of emotional well-being. Conclusion: A parent with social support resources and higher levels of hope experiences higher levels of positive perceptions regarding their child's illness. Higher levels of positive perceptions allow the parent to express more positive than negative emotions, thus maintaining a more optimal level of subjective emotional well-being. The findings offer implications for healthcare teams to enhance sensitivity to parents’ needs and to help parents attain more resources, positive perceptions, and well-being.